ANALISIS LABA, ARUS KAS, DAN LIKUIDITAS UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS Pada Perusahaan Manufaktur Sektor Tekstil yang Tercatat di Bursa Efek Indonesia Tahun 2019-2021 - Petrus Adi Kurniawan (Student Research Journal, 2023)
This study aims to examine the effect of earnings, cash flow, and liquidity in predicting financial distress in textile manufacturing companies. This study uses a quantitative descriptive analysis model. Data was obtained from secondary data, namely data obtained from other parties in the form of publication reports for the 2019- 2021 period. The population in this study are textile companies listed on the Indonesian Stock Exchange. The number of samples in this study are as many as 10 companies. The sampling method used was purposive sampling. The data is processed using SPSS, based on the conclusions of the analysis it is known that: (1) the t test shows that partially the profit and cash flow variables have no effect on financial distress, while liquidity has a positive and significant effect on financial distress; (2) the F test shows simultaneously the variables of profit, cash flow, and liquidity have an effect on financial distress; (3) the R2 test shows that the Adjust R value is 0.652 meaning that the variables of profit, cash flow and liquidity simultaneously affect financial distress by 65.2%, while the remaining 34.8% is influenced by other factors.